Pengaruh Kualitas Pelayanan, Kualitas Produk, Harga, Dan Lokasi Terhadap Kepuasan Konsumen ( Studi Kasus Pada Konsumen Kafe Family Kopi Di Malang ) - Winda Jaya; Rois Arifin; Afi Rahmat Slamet (UNIVERSITAS ISLAM MALANG, 2021)
ABSTRACT The coffee shop business in Indonesia is currently growing, this can be seen from the significant increase in the number of coffee shops in Indonesia in the last three years. Even though the coffee consumption of the Indonesian people is low, the majority are coffee lovers and most coffee lovers are not only men but women also like it. Quoted in (beritasatu.com) The coffee trend in 2020 will continue to grow and this growth is supported by several factors, such as the habit (culture) of hanging out while drinking coffee. This study aims to determine the effect of service quality, product quality, price and location on customer satisfaction. The population of this research is the consumers of Malang Coffee Family Café, with a sample size of 89 respondents who were selected using purposive sampling technique. Hypothesis testing in this study uses multiple linear regression analysis. The results showed that the variables service quality, product quality, price and location simultaneously affect customer satisfaction. The variables of product quality and price have a positive and significant effect on customer satisfaction, while the variables of service quality and location have a positive and insignificant effect on customer satisfaction. Keywords: Service Quality, Product Quality, Price, Location and Customer Satisfaction.